Toxic-ions catalyzed hidrolysis of amoxicillin: HPLC kinetics studies - Doadrio Villarejo, Antonio Luiz; Solelo, José B.; Doadrio, Juan Carlos; Orenga, Regina; Mayorga, Antonio (Eclética Química, 1994)
.